The Influence of Location and Attractiveness on Visiting Decision (Study on Majalengka Paralayang Tourism Object) - Patimah, Endang Siti; Masduki,; Sopiyan, Pipih; Hidayat, Gustina (Finance and Business Management Journal, 2023)
Along with the current market competition, not only the product sector but also the tourism sector. One of the attractions that can win the competition for tourist visits is one that has a strategic location that is easily accessible and the tourist attractions that exist on the tour. This study aims to determine the effect of location and tourist attraction on the decision to visit visitors to paragliding attractions partially. This research method is a survey research using a descriptive and verification approach. The population in this study were visitors to paragliding attractions with as many as 100 respondents, the sampling technique used was incidental sampling technique. The data collection technique in this study used a questionnaire using the Likert scale. The analysis tool uses classical assumption test, multiple regression analysis, coefficient of determination analysis, partial test and model feasibility test. Based on partial hypothesis testing, location and tourist attraction have a positive and significant effect on visiting decisions. This means that the location and tourist attraction become an impulse factor in increasing people's decisions to visit tourist sites.